A aplicabilidade do código de processo civil no processo administrativo tributário estadual. - Ramos, Mário de Godoy (2022)
The Civil Procedure Code determines in art. 15, that its provisions are applied in administrative proceedings, of which the tax administrative proceedings are a type, in a subsidiary and supplementary manner. However, CPC is an ordinary Federal Law, published under nº 13,105 of 2015, and its validity and incidence basis is not clear for automatic observation and application by subnational entities due to the federative autonomy of each State. The applicability of the CPC in the tax administrative proceedings (PAT) of each State of the Federation of Brazil is investigated, especially because 9 (nine) States are silent in their legislation regarding the applicability of the CPC. The direct unconstitutionality action (ADI) nº 5.492/RJ, which is being processed at the Federal Supreme Court, challenges the constitutionality of art. 15 of the CPC due to the federative autonomy of subnational entities. If the applicability is legitimate, the CPC is supplementary and subsidiary applicable, in view of any legal gaps in the PAT Law that would authorize the use of the CPC by tax administrative judges. The work aims to reflect on the legitimacy of this normative integration. The conclusion is that there is no offense to federative autonomy, since the local norm must be applied primarily. Only in the case of legal gaps would be needed normative integration for which the CPC’s provisions will be applied subsidiarily or supplementary. It’s also needed a judgment of compatibility of the residual norm with local legislation. Especially, CPC must be applied when the normative integration implies to the effectiveness of procedural constitutional guarantees.